2022
DOI: 10.1155/2022/3586064
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Alpha-Fetoprotein and Association with Mortality in Hepatocellular Carcinoma of HIV-1-Infected Patients

Abstract: Background and Aim. The clinical course of hepatocellular carcinoma (HCC) is determined by cancer-related and nonrelated factors. We evaluated the effect of a cancer-related factor, alpha-fetoprotein (AFP) levels, on mortality in HIV-1-infected patients with HCC. Methods. This is a retrospective cohort study on patients living with HIV-1 infection (PLWH) followed at the Division of Infectious Diseases of the San Raffaele Hospital, with cirrhosis and HCC diagnosed between 1999 and 2018 and with an available AFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We previously showed that, among participants with advanced BCLC (stage D) and low liver functional reserve (CPT B/C), treatment discontinuation due to adverse events occurred in a minority of participants, suggesting that systemic treatment with sorafenib is well tolerated in PLWH, despite advanced HCC stage ( 10 ). Conversely, the presently reported two cases with a good liver functional reserve and an intermediate BCLC score showed low tolerability to systemic treatment with lenvatinib.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that, among participants with advanced BCLC (stage D) and low liver functional reserve (CPT B/C), treatment discontinuation due to adverse events occurred in a minority of participants, suggesting that systemic treatment with sorafenib is well tolerated in PLWH, despite advanced HCC stage ( 10 ). Conversely, the presently reported two cases with a good liver functional reserve and an intermediate BCLC score showed low tolerability to systemic treatment with lenvatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, we showed in PLWH with HCC that AFP at a precise cut-off is associated with a worse prognosis, considering all treatment options [ 22 ]. In the present study, which included PLWH who received IT, the AFP at values < 28 ng/mL emerged as an independent survival-related factor, confirming the importance of this biological marker in the prognosis of HCC also at an early stage since 48% of participants had BCLC 0/A.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-fetoprotein levels were also stratified according to the cut-off levels of 28 ng/mL, which we previously found associated with survival in PLWH with HCC [ 22 ]. Hepatitis B, C, and Delta infections were assessed by the presence of hepatitis B surface antigen [HBsAg], hepatitis C, and hepatitis Delta antibody positivity (anti-HCV and anti-HDV, respectively).…”
Section: Methodsmentioning
confidence: 99%